5 ( x – 3 ) – 4 ( x + 2 ) = 3 ( 1 – 2 x ) + 4
Soluções para a tarefa
Respondido por
0
Resposta:
5 ( x – 3 ) – 4 ( x + 2 ) = 3 ( 1 – 2 x ) + 4
5x - 15 - 4x - 8 = 3 -6x +4
5x + -4x + 6x = 3 + 4 + 15 + 8
7x = 30
x = 30/7 ou 4 ou 4,29
Explicação passo-a-passo:
Respondido por
0
Resposta:
5x-15-4x+8=3-6x+4
5x-4x+6x=3+4+15-8
7x=14
x=14/7
x=2
Anexos:
![](https://pt-static.z-dn.net/files/d64/a8366f2ca1ed64070dd0714c027f8f6d.jpg)
Perguntas interessantes
Inglês,
9 meses atrás
Matemática,
9 meses atrás
Português,
1 ano atrás
Filosofia,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás